Das Siedlungsbild der Peloponnes um das Jahr 1700.: Mit einer Karte und einem Ortsverzeichnis - Sauerwein, Friedrich (ERDKUNDE, 1969)
The aim of the investigation is a reconstruction of the settlement pattern of the Peloponnese around the year 1700. The most important source is the inventories made by the Venetians after they conquered the area in 1685 and published by PACIFICO in 1704. Over 80% of the places mentioned have been assembled, with the help of maps, old travel accounts and statistics, into a gazatteer, located and placed onto the accompanying map. Difficulties arise in this respect through writing errors on the part of chroniclers (Greek and Latin letters) and in the renaming of many places which has meanwhile occurred. Within the Venetian administrative boundaries the map clearly shows concentrations of settlement in the historically and economically important parts of the area. The villages were, admittedly, small. The mean population total per settlement was about 127 and this includes the larger fortified towns.